Estudo de caso aplicado a logística reversa de pneus inservíveis no município de Porto Velho/RO - Moreira, Marcos Vinicius Carneiro (Universidade do Vale do Rio dos Sinos, 2021)
This study aims to evaluate the application of the reverse logistics of waste tires in the city of Porto Velho-RO, based on the diagnosis of the process and guided by the principles and guidelines of Law No. 12,305 - National Solid Waste Policy (PNRS) for a Solid Waste Management Plan (PGRS) and as recommended by CONAMA (National Solid Waste Council) Resolutions No. 258/1999 and No. 416/2009. The proposed methodology involves field research in the municipality and refers to a quali-quantitative approach, which is configured in a case study, and in which the current situation of actions taken to manage waste tires was evaluated. The research had as steps the identification of the agents involved, diagnosis of waste tire management in the municipality, the survey of environmental aspects and impacts based on the sources of generation, final disposal and quantification of waste, the identification of failures and opportunities for improvement based on the requirements for compliance with CONAMA Resolutions No. 258/1999 and 416/2009 and on the requirements for compliance with legislation. The study also aimed at proposing guidelines for the management of these wastes in the municipality with a view to their use as raw material. The results obtained from the survey show that most companies evaluated receive tires that are not in use. It is observed that most companies do not receive support from suppliers, which implies the lack of information about the reverse logistics of waste tires. As guidelines, and based on the diagnosis carried out through exploratory research via a questionnaire in interviews, it is proposed that companies provide training courses on the PNRS and awareness of the importance of proper management of waste tires; it is proposed that the autarchies carry out the increase in the number of ecopoints scattered in strategic locations in the municipality and also draw up monitoring and inspection plans for both the collection and the final destination of these wastes.
Keywords: Resíduo sólido; Logística reversa; Pneus inservíveis; Reciclagem; Solid waste; Reverse logistic; Waste tires; Recycling; ACCNPQ::Engenharias::Engenharia Civil